Cost-effectiveness Analysis of Reference Infliximab (Remicade) Compared to its Biosimilar (Remsima) in Iraqi Patients with Rheumatoid Arthritis (Conference Paper )# - Fadhil, Hasan Raid; Al-Jumaili, Ali Azeez; Al-Ani, Nizar Abdulateef (Iraqi Journal of Pharmaceutical Sciences, 2023)
The study objective was to conduct Pharmacoeconomics study (cost-effective analysis) between infliximab reference (Remicade) and its biosimilar (Remsima) in patients with rheumatoid arthritis (RA) in Iraqi hospitals. This is a retrospective multicenter pharmacoeconomic analysis conducted at two large teaching governmental hospitals in Baghdad, Iraq which provided infliximab to patients with RA. Data were collected from patient’s medical records and face-to-face interviews with the patients from December 2021 to April 2022. The study included 57 patients with rheumatoid arthritis (RA). The patients were categorized into two groups according to the type of infliximab they received over 30 weeks: 27 patients received reference infliximab (Remicade) and 30 patients received biosimilar infliximab (Remsima). The two groups had comparable demographic and baseline disease parameters, with a mean age of 49.6 years and a BMI of 30.0. The vast majority of participants were women (82.5%) with low level of formal education (65%). Overall, both infliximab biopharmaceuticals had good effectiveness to reduce the RA disease activity (CDAI) and improve patient quality of life. They both had comparable adverse reactions including UTI, fatigue, and headache. There was no significant difference (P-value >0.05) in disease activity between the two groups according to RA clinical disease activity index (CDAI) score across all three-time measures: before biological therapy, 14 weeks post-therapy and 30 weeks post-therapy. In 2019, Remicade was slightly more effective and provide better quality of life, but costlier (41,896 per QALY) compared to Remsima. It was not clear whether the reference biologic (Remicade) or its biosimilar (Remsima) was more cost effective. In 2021, Remicade was more cost effective compared to Remsima because Remicade was less expensive and relatively more effective according to CDAI and EQ-5D-5L scores. Registering and purchasing both reference infliximab and its biosimilar was good idea to keep the competition in the price and maintain infliximab for RA patients.